Impact of environmental and plant factors on Aspergillus section Flavi isolated from maize in Italy - Giorni, Paola (Cranfield University, 2007)
The exceptional hot weather conditions in Italy during the summer of 2003 resulted in an optimal environment for the development of Aspergillus section Flavi in maize and, consequently, for aflatoxin production. This caused significant contamination, above the EU legal limits, for maize destined to feed and food. This study was focused to define the distribution of these fungi in Italy for the first time. In all the sampled regions of Northern Italy, A. flavus was present. Ecological studies were conducted and this defined the cardinal conditions of water availability (0.83-0.99 aw), temperature (15-45°C) and gas composition (CO2<50%) for sporulation, growth and aflatoxin B1 production. Since in the field A. flavus does not occur alone, possible interactions with the fumonisin producing species Fusarium verticillioides was examined by using carbon source utilisation patterns and niche overlap indices. F. verticillioides was a better competitor over the range 0.93-0.98 aw and temperature of 20°C while A. flavus dominated at 0.98 aw and 30°C. Inoculum concentration (10 1 -10 7 CFUs ml) affected infection efficiency, with a low percentage of kernels becoming infected with up to 10 5 conidia mL -1 , and early maize growth stages were more susceptible. A total of 34 maize hybrids were screened for resistance to A. flavus and aflatoxin production and this showed that about 40% of these showed promise. The data sets obtained in this study wil provide a powerful basis for the development of a Decision Support System to minimize aflatoxins in maize.